2012
DOI: 10.1016/j.febslet.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive autotaxin transcription by Nmyc‐amplified and non‐amplified neuroblastoma cells is regulated by a novel AP‐1 and SP‐mediated mechanism and abrogated by curcumin

Abstract: a b s t r a c tThe motility, angiogenesis and metastasis-stimulating factor Autotaxin (Atx), over expressed by human neuroblastomas (NB), is constitutively expressed by human Nmyc-amplified SK-N-BE and non-Nmyc-amplified SH-SY5Y NB cells. Here, we characterise a novel Atx transcriptional mechanism, utilised by both cell lines, that is restricted to the first 285 bp of the Atx promoter and involves AP-1 and SP transcription factors, acting through a CRE/AP-1-like element at position À142 to À149 and a GAbox at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…L1 cell adhesion molecule (L1CAM) was the fourth most abundant protein in SK-N-BE2 (72-fold highly abundant compared to SH-SY5Y) and is known to be an indicator for developing neuronal cells in more mature stages of neuroblastoma [ 26 ]. The motility, angiogenesis and metastasis-stimulating factor Autotaxin (ENPP2) [ 27 ], was 65-fold enriched in SK-N-BE2. Similarly, dopa decarboxylase (DDC) was 28-fold highly abundant in SK-N-BE2.…”
Section: Resultsmentioning
confidence: 99%
“…L1 cell adhesion molecule (L1CAM) was the fourth most abundant protein in SK-N-BE2 (72-fold highly abundant compared to SH-SY5Y) and is known to be an indicator for developing neuronal cells in more mature stages of neuroblastoma [ 26 ]. The motility, angiogenesis and metastasis-stimulating factor Autotaxin (ENPP2) [ 27 ], was 65-fold enriched in SK-N-BE2. Similarly, dopa decarboxylase (DDC) was 28-fold highly abundant in SK-N-BE2.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that the ENPP2 gene is devoid of typical TATA or CAAT motifs at the 5 ′ region but contains putative binding sites for at least four transcription factors, including Max1, HNF-3B, AP, and Sp1, and a probable octamer binding locus in intron 2. In addition, studies in neuroblastoma cells showed that AP-1 and Sp3 transcription factors control ATX expression by binding to CRE/AP-1-like and GAbox elements at the upstream regulatory regions ( 41 ). A more recent study suggests that ATX gene transcription GTP 5 ′ ␤ -phosphates, hydrolyzes the AMP group from the NAD molecule, and functions as an ATP pyrophosphatase by removing the entire pyrophosphate group from nucleoside phosphate molecules ( 3 ).…”
Section: Transcriptional Control and Secretionmentioning
confidence: 99%
“…Previous work has demonstrated that over‐expression of v‐Jun induces autotaxin in chick embryo fibroblasts . c‐Jun and JunD bind to a CRE/AP1‐like site in the autotaxin promoter and enhance promoter activity, suggesting that autotaxin may be a direct c‐Jun target .…”
Section: Resultsmentioning
confidence: 99%